2015
DOI: 10.1667/rr13831.1
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Mitigates Radiation-Induced Pulmonary Fibrosis

Abstract: Triptolide (TPL) may mitigate radiation-induced late pulmonary side effects through its inhibition of global pro-inflammatory cytokines. In this study, we evaluated the effect of TPL in C57BL/6 mice, the animals were exposed to radiation with vehicle (15 Gy), radiation with TPL (0.25 mg/kg i.v., twice weekly for 1, 2 and 3 months), radiation and celecoxib (CLX) (30 mg/kg) and sham irradiation. Cultured supernatant of irradiated RAW 264.7 and MLE-15 cells and lung lysate in different groups were enzyme-linked i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…Our previous study showed that macrophage inflammatory protein-2 (MIP-2), which plays an important role in inflammatory cell migration [ 18 ], was the dominant chemokine in irradiated lung tissue [ 9 ]. As such, we examined the effect of TPL on MIP-2 production.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous study showed that macrophage inflammatory protein-2 (MIP-2), which plays an important role in inflammatory cell migration [ 18 ], was the dominant chemokine in irradiated lung tissue [ 9 ]. As such, we examined the effect of TPL on MIP-2 production.…”
Section: Resultsmentioning
confidence: 99%
“…Although a report of pharmacokinetics of TPL in C57BL/6 mice is lack, logically the administration of TPL (0.25 mg/kg, IV) would reach a plasma concentration higher than 2 ng/ml. Furthermore, our previous in vitro dose-dependent study with 2, 5 and 10 ng/ml TPL indicated that all three doses inhibited cytokine production, with the most striking effect at 10 ng/ml [ 9 ]. To ensure an obvious effect while avoiding toxicity as well as to utilize concentrations close to those needed in vivo , we ultimately selected 5 ng/ml.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Triptolide treatment has been shown to inhibit lung inflammation and injury in multiple lung disease models, including lipopolysaccharide injury (Wei and Huang, 2014), pulmonary fibrosis induced by radiation (Yang et al, 2015) or bleomycin (Krishna et al, 2001), and allergic inflammation and airway remodeling (Chen et al, 2011; Chen et al, 2015). In the present study, three of the triptolide formulations that were tested in vivo produced significant inhibition of chlorine-induced inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the triptolide in a xenograft model of mouse pancreatic cancer showed an anticancer effect by downregulating of 11 genes, including c-myc, SRYrelated HMG-box 9 (SOX9) and ETS proto-oncogene 2 (Ets2), and an over-expression of c-myc in colon cancer cells promotes increased expression of HIF-1α and VEGF (Ding et al, 2015). Triptolide (0.25 mg/kg; i.v., 2 times/week for 1, 2 and 3 months) in C57BL/6 mice was also found to reduce a mitigated radiation-induced pulmonary fibrosis (Yang et al, 2015b). Additionally, this diterpene also exerted an anticancer effect via reverse transcriptase component of telomerase (hTERT) transcription, possibly by inhibiting transcription factor specificity protein 1 (Sp1) in primary effusion lymphoma cells (Long et al, 2016).…”
Section: Miscellaneous Effectsmentioning
confidence: 97%